1968
DOI: 10.1007/bf00175119
|View full text |Cite
|
Sign up to set email alerts
|

Topside sounding of the earth's ionosphere

Abstract: The evolution of topside sounding through rocket and satellite experiments is reviewed. Topside sounding has proved valuable for revealing the structure of the high ionosphere and for investigating the resonance properties of a magnetoplasma. The limits of our present knowledge of these rapidly developing subjects are discussed. Topside sounding is predicted to have a long and useful role in exploration of the ionosphere of earth and other planets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…These data could be used to determine electron density profiles down to the peak below each satellite, and at the midpoint between them. In the simulated Chapman and Warren (1968). Illustration of the ionospheric topside sounding technique, showing method of ionospheric density-altitude profile observation using swept-frequency transmissions.…”
Section: Networked Sounding From Spacementioning
confidence: 99%
“…These data could be used to determine electron density profiles down to the peak below each satellite, and at the midpoint between them. In the simulated Chapman and Warren (1968). Illustration of the ionospheric topside sounding technique, showing method of ionospheric density-altitude profile observation using swept-frequency transmissions.…”
Section: Networked Sounding From Spacementioning
confidence: 99%
“…Lawrence et al (1964) and Millman (1967) have published reviews on propagation effects on trans-ionospheric signals, and reviews on the three "generic" uses of earth satellites to measure ionospheric characteristics (TEC and scintillations of beacon signals, and topside sounding) are given by; Chapman and Warren (1968), Evans (1977), Davies (1980), Jackson et al (1980), Aarons (1982), Yeh and Liu (1982). Until the advent ofthe high altitude rockets, satellites, and incoherent-scatter sounders, the topside ionosphere was inaccessible by standard ground-based radio techniques.…”
Section: Satellite Radio Experimentsmentioning
confidence: 99%
“…Reviews of topside sounder technology and results of early investigations are reported in the Special Issue of JATP of November, 1967, by Chapman and Warren (1968), and in the Special Issue ofthe Proceedings ofthe IEEE of June 1969 (guest editors, Schmerling and Langille) also by Benson and Bitoun (1979).…”
Section: Satellite Topside Soundersmentioning
confidence: 99%
“…If we observe and monitor the variation in these parameters, we may estimate the ionospheric impact on the transionospheric radio applications. For this reason, ionospheric conditions, including the F 2 layer, have been monitored with various observation equipment, such as worldwide ionosonde networks (e.g., Galkin et al, 2006), incoherent scatter radars (e.g., Gordon, 1958), topside sounding (e.g., Chapman & Warren, 1968), and radio occultation from satellites (e.g., Hajj et al, 1994; Hardy et al, 1994). However, these observations not only have limitations in terms of time and spatial resolutions but also cannot predict future conditions.…”
Section: Introductionmentioning
confidence: 99%